2022
DOI: 10.1096/fj.202200410r
|View full text |Cite
|
Sign up to set email alerts
|

The Ldb1 transcriptional co‐regulator is required for establishment and maintenance of the pancreatic endocrine lineage

Abstract: Pancreatic islet cell development is regulated by transcription factors (TFs) that mediate embryonic progenitor differentiation toward mature endocrine cells. Prior studies from our lab and others showed that the islet‐enriched TF, Islet‐1 (Isl1), interacts with the broadly‐expressed transcriptional co‐regulator, Ldb1, to regulate islet cell maturation and postnhyperatal function (by embryonic day (E)18.5). However, Ldb1 is expressed in the developing pancreas prior to Isl1 expression, notably in multipotent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…At P1, pancreata were collected, weighed for pancreatic mass index calculation (pancreas weight/total body weight × 100 [ 20 ]), and formaldehyde fixed for histology. Trunk blood was collected from P1 and P10 mice and blood glucose measured using an automatic glucometer (Bayer Contour Next).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At P1, pancreata were collected, weighed for pancreatic mass index calculation (pancreas weight/total body weight × 100 [ 20 ]), and formaldehyde fixed for histology. Trunk blood was collected from P1 and P10 mice and blood glucose measured using an automatic glucometer (Bayer Contour Next).…”
Section: Methodsmentioning
confidence: 99%
“…The widely-expressed transcriptional co-regulator LIM-domain binding protein-1 (Ldb1) interacts with LIM-HD TFs, including Isl1, to impact transcription of diverse genes during development [ 18 ]. In the pancreas, our lab and others have shown that robust Ldb1::Isl1 interactions are required for islet-cell identity and function both during development and in the adult β-cell [ 16 , 19 , 20 ]. Ldb1 contains a dimerization (DD) and LIM-interaction domain (LID) allowing it to act as a dimerized scaffold for stabilizing large transcriptional complexes.…”
Section: Introductionmentioning
confidence: 99%